Upaya Pelatihan Dan Pengenalan Tari Tradisi Gaya Surakarta Di SMA Batik I Surakarta - Dwi Rahmani (Institut Seni Indonesia Surakarta, 2016)
The article entitled â€œAn Attempt to Train and Introduce A Traditional Dance of Surakarta Style in SMA Batik I Surakartaâ€ is the result of a public service activity. Dance education is hoped to be able to be successful as one of the supporting pillars of Javanese art and culture in Surakarta. A traditional dance is art and cultural heritage being the characteristics and identity of the court of Surakarta. The problem is that the sophisticated and modern stream of globalization has influence over the life of traditional dance, especially over the younger generation. Due to that, the dance training for senior high school students is hoped to be able to make them more appreciative to traditional dance. The methods used in the training were drill, demonstration, lecture, and synthesis analysis structure. Based on the methods, the result of the training shows that the students could present a story called Rara Mendut Pranacitra, a collaboration of theatre, dance and karawitan. They were only trained for four months but the performance was good enough according to the evaluation criteria for a work of dance.Keyword : traditional dance, trainning , appresiation